Uji Minda

Diberi a = b
a^2 = ab
a^2 – b^2 = ab – b^2
(a+b)(a-b) = b(a-b)
(a+b) = b
(a+a) = a, sebab a = b
2a = a
2 = 1 !!! Kenapa? Sila jelaskan.

** a^2 bermakna ‘a kuasa 2′

About these ads

5 responses to “Uji Minda

  1. Just giving a try..hehehe =)

    Given a=b,
    a^2=ab

    a^2-b^2=ab-b^2
    (a+b)(a-b)=b(a-b), because (a+b)(a-b)=a^2-b^2
    a^2-b^2=ab-b^2
    a^2-b^2=b(a-b)

    then,
    (a+b)=b, because (a+b)(a-b)=b(a-b)
    can ‘cancel’ the (a-b)on both sides

    a+b=b
    since a=b,
    a+a=a
    2a=a
    2=1 since a divide a is 1

    • hussenhmhuda

      TQ Vanessa… Can u tell me, what is the value of (a-b)? And, can we divide the equation
      (a+b)(a-b)=b(a-b) with (a-b)? Think…think…think…

      • wahahahahaha…. yalah yalah tchr….

        haiyo… ya kan, what a careless mistake… consider ok la kan…. 4 months didn’t do any maths… very very rusty already…. makan, tidur, tengok tv everyday… no input at all this few months. Well, i’ll make sure i figure this question out SOMEDAY SOON!!! Look out for a reply! Hehehehehe =)

        (By the way, sejak bila pula cikgu2 maktab ada blog ni?! My my)

  2. [InF]^RaZz[YaMaTeH]

    (a+b)(a-b) = b(a-b)
    (a+b) = b <<<(a+b) is not equal to b , u can’t remove (a-b) as it is sticking wif b , b(a-b) *only the b can be “cut” , whereas (a-b) cannot *

    cuz (a+b)(a-b)=b(a-b)
    therefore , a^2-ab+ab-b^2=ab-b^2
    a^2=ab
    a(a)=ab , since a=b ,
    a(a)=a(a) ~!

    (a-b),
    since a = b ,
    (a-b) = a-a
    a-a = 0

  3. [InF]^RaZz[YaMaTeH]

    if u divide by (a-b) which is 0 … u get INFINITY ~!!$# [InF] =]

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s